Single aperture multiple optical waveguide transceiver - LECLAIR LANCE RICHARD; MAMIDIPUDI PRIYAVADAN (2012)
A single-aperture, multi-axial transceiver is provided that is particularly useful in a LIDAR system for detecting low velocities at increased ranges. The system is particularly useful in systems that are required to measure very low velocities and very short distances as well as to provide an operating range of hundreds of meters. The transceiver uses closely spaced waveguides placed near the focal point of a single objective 8 to form input and detector apertures. Preferably the input and detector apertures are spaced from each other by less than about 80 μm. In an embodiment using light with a wavelength of 1550 nm, the spacing is preferably about 30 μm.